The ghosts of Paris : a novel - Moss, Tara (Dutton, an imprint of Penguin Random House LLC, 2022)
"A thrilling tale of courage and secrets set in postwar London and Paris, in which a search for a missing husband puts investigator and former war reporter Billie Walker on a collision course with an underground network of Nazi criminals"--